Karakter Ornamen dan Manifestasi Budaya - Ghozali, Mahbub (SUHUF, 2024)
This study aims to discern the arrangement patterns of ornaments that give illumination a distinctive character in the Qur’anic manuscript in Madura. Employing a qualitative method and utilizing a history of the idea analysis process, this research reveals a significant correlation between the ornamental features in the Qur’anic manuscripts and the carving art patterns that flourished in Madura during the 19th century. The per-samper structure as an edge decoration, onggelan in the creation of floral motifs, and the incorporation of chakra motifs on the koseko (corner) attest to the representation of a unique carving culture inherent in Madurese art, as manifested in the illuminated Qur’anic manuscript. The illustrator forms simple patterns and image structures by omitting detailed ornaments. The simple shapes and patterns are identified as the impact of the abstraction model of art products through imitation. Nevertheless, the dominant aspect that shows a distinctive artistic tendency in the Madurese tradition is represented in the use of colors that are characteristic of Madurese color selection in their art products.